PENGARUH PERPUTARAN PERSEDIAAN BARANG TERHADAP LABA USAHA SWALAYAN BERSKALA BESAR DI KOTA BANDA ACEH - Surya, Zen (Universitas Muhammadiyah Aceh, 2009)
The aimed of research are to measure return on investment at big scale supermarket in Banda Aceh. The research do for Banda Aceh Industrial and Trading Agency registered supermarket, using selected criteria such as financial report, have trading capital up to 500 millions, have advantage and do purchasing 2 times in month. Based on 30 supermarket in Banda Aceh who fulfill the criteria, received 4 supermarket sample in this project. Analyze technical data using in this project are simple linear regression: Y=α+βX+ε elaborate with statistical analyze using statistical program for social science (SPSS). Data in this research use data from 2008 data compile with several financial report by 4 supermarket sample. Analyze from research with SPSS showing return on investment in the big scale supermarket result with the formula Y=35,250 +0, 95 X with Y are advantage and X are return on supplies, with hypothetical t count > t table (4,403>3,182). From this test showed return on investment have positive influence and significant to earnings of big scale supermarket in Banda Aceh. Independent Variable influence with dependent variable are 90, 6% and 9, 4% influence by other variable out of research. Keyword : return on investment, earnings DAFTAR KEPUSTAKAAN Dyckman, et.al. (2000) “Akutansi Intermediate” Edisi Ketiga, Jilid I. Alih bahasa Munir Ali,SE,MBA. Penerbit Erlangga, Jakarta Harahap Sofyan Syafri (1998) “Analisa Kritis Atas Laporan Keuangan” Edisi pertama, Penerbit Salemba empat, Jakarta. Hadibroto, S. dan Witarsa Omar. (2002) “Sistim Pengamanan Intern”,Jakarta Fakultas Ekonomi Universitas Indonesia Ghozali, Imam (2001) “Aplikasi Analisis Multivariate dengan Program SPSS,” Edisi I. Semarang Hendrikson,S.Eldon (2002) “Akutansi Untuk Usahawan” ,Jakarta : Lembaga penerbit Fakultas Ekonomi Universitas Indonesia. Harnanto (2003), “Laba” www.google.com. Accesed April 24,2009.15.30 Ikatan Akutansi Indonesia (2002) “Standar Akutansi Keuangan” Buku Satu, Penerbit Salemba Empat, Jakarta Kania (2006) “Pengaruh Tingkat Perputaran Persediaan Barang Jadi Terhadap Tingkat Rentabilitas Pada PT. Pindad (Persero) Bandung” Jurusan Pendidikan Akutansi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Indonesia Keiso. James (2002) “Akutansi Intermediete” Volume komprehensif, Jakarta. Erlangga Madriqah (2005). “Sistim Akutansi Persediaan Bahan Baku pada PT.Sinar Lando Ambarawa” Jurusan Ekonomi, Fakultas Ilmu Sosial Universitas Negri Semarang. Nida (2008) “Pengaruh Perputaran Persediaan Terhadap Barang Jadi Terhadap Modal Kerja Pada PT. Inti (Persero)” Jurusan Akutansi Fakultas Ekonomi Universitas Widyatama. Prastowo, Dwi dan Rfka Julianti (2002) “Analisis Laporan Keuangan (Konsep Dasar Aplikasi)” .Yogyakarta : UUP AMP YKPN. Rustam, (2002) “Pendapatan Menurut Standar Akutansi Keuangan No.23” Jurusan Akutansi, Fakultas Ekonomi, Universitas Sumatra Utara Skousen, K. Fred, Stice, James.D. (2001) “Akutansi Keuangan Menengah” Volume Komprehensif, Jakarta, Salemba Empat. Smith, Jay M. and K.Fred Skousen (2002) “Intermediete Accounting” Volume komprehensif, edisi kedelapan, Jakarta: Penerbit Erlangga . Soemarso,S.R (2000) “Akutansi Suatu Pengantar” Buku Satu, Jakarta : Lembaga Penerbit FEUI. Yenti (2004) “Rancang sistim informasi Persediaan bahan baku Terkomputerisasi PT.KPL” Jurusan Ekonomi Manajemen, Fakultas Ekonomi-Universitas Kristen Etra. Weston, J. Fred and Copeland, Thomas E. (2001) “Managerial Finance” 8 th Edition CBS College Publishing. Zaki Baridwan (2002) “Intermediete Accounting” Edisi ketujuh BPFE, Yogyakarta.